STRATEGI PEPERANGAN KHALID BIN WALID DALAM PERANG MU’TAH DAN PERANG YARMUK - Tazkiyyatur Rohmah (JSI: Jurnal Sejarah Islam, 2022)
This paper aims to examine Khalid bin Walid’s war strategy in the Mu’tah war and the Yarmuk war. The method of writing this article is by reviewing literature from journals and books that write the history of Khalid bin Walid. The results of this study reveal that the Mu’tah war was the first war that Khalid bin Walid participated in after converting to Islam. The strategy used by Khalid bin Walid in this war included regrouping the Muslim troops after they were devastated by the loss of their leaders, then making small incidents by measuring the time of the war until the night, and camouflaging the troops for their war tactics. While in the Yarmuk war, this war involved Arab Muslim troops against the troops of the Byzantine Empire. The Yarmuk war took place in a valley called Yarmuk, Jordan. Khalid bin Walid’s strategy in this war was to form a kurds or battalion and the troops were made into thirty-five to forty kurds. Each Kurd consists of a thousand people led by the leader of the army.